Concentration limits of niobium and cadmium alloys existence, formed by ultrafine particles - Volodin, V.N.; Tuleushev, Yu.Zh.; Nitsenko, A.V.; Burabaeva, N.M. (Kompleksnoe Ispolzovanie Mineralnogo Syra = Complex use of mineral resources, 2019)
Cd metals are established to form an alloy with a body-centered cubic structure up to a 64.5 at. % concentration as a result of determining the limits existence of Cadmium in Niobium solid solutions, obtained by plasma-assisted ion sputtering and ultrafine particles co-precipitation to a critical size. At this, two linear dependence sections in the range of 0 – 50.0 at. % and 50.0 – 64.5 at. % of Cadmium (the rest is Niobium) are found described by the equations a [nm] = 8•10-5x +0.3306 and a [nm] = 3•10-4x +0.32188 (respectively), where x is the Cadmium content in the alloy, at. %. At 68 at. % of Cadmium, an unknown phase was identified; no solid solutions of Niobium in the Cadmium were detected. The growth of the lattice parameter is due to the fact, that Cadmium atoms have a larger radius than Niobium atoms: (ra)Cd = 0,1727 нм, (ra)Nb = 0,1625 nm. The kink on the linear dependence of the lattice parameter of the Cadmium in Niobium solid solution as a result of Cadmium concentration in the alloy is explained by the fact that Cadmium first replaces the Niobium atom in the center of the unit cell, then is also embedded in the Niobium lattice with increasing its concentration replacing the Niobium atom in one of the cube vertices. The latter causes a more intense increase in the size of the unit cell. The possibility of the alloys formation in a wide range of concentrations as a result of thermal-fluctuation melting and the merging of very small unlike particles that have significant differences in physical properties, metal particles was confirmed, which is unattainable with the traditional thermal production method.